2018
DOI: 10.1002/cdq.12131
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Career Planning on Career Thoughts in STEM‐Interested Undergraduates

Abstract: Undergraduate career planning courses have shown efficacy in decreasing students’ negative career thoughts; however, universities have minimally applied these courses to science, technology, engineering, and math (STEM) populations. This study compared the influence of a STEM‐focused career planning course for undecided STEM students with a seminar course for decided STEM majors. An analysis of covariance with covariate adjustment revealed that undecided career planning students had lower adjusted mean scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…The study's preliminary results revealed a low level of satisfaction with their academic major and high negative career thoughts. These results concur with prior studies that indicated that uncounseled college students, as well as those who had no guidance on career planning in their http://www.scientiasocialis.lt/bjcem major, had no reduced negative career outlook/thoughts (Alchin, Mcllveen, & Perera, 2018;Belser et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The study's preliminary results revealed a low level of satisfaction with their academic major and high negative career thoughts. These results concur with prior studies that indicated that uncounseled college students, as well as those who had no guidance on career planning in their http://www.scientiasocialis.lt/bjcem major, had no reduced negative career outlook/thoughts (Alchin, Mcllveen, & Perera, 2018;Belser et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Future work would need to be conducted to investigate these assumptions in the BME context as there is extensive research that career planning courses support career exploration and engagement for undergraduates students in higher education 29 including a few studies of STEM majors. 3 , 4 , 28 Given the multiple career paths in BME, programs could structure courses to include opportunities for students to discuss how different content and skills apply and are useful in a variety of careers. This is particularly important considering the already documented discrepancy between BME curricula and stakeholder expectations of BME graduates.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of self-efficacy on various stages of career planning (exploration, decision-making, and job search) is one of the most consistently supported findings in the literature. There is some evidence that career management training can help enhance such self-efficacy (Jackson & Wilton, 2016) and reduce negative thoughts about career (Belser, Prescod, Daire, Dagley, & Young, 2018). As noted earlier, feedback is an important contributor to self-efficacy (Bandura, 1977;, as well as leading to the setting of more challenging goals (Donovan, 2009).…”
Section: Implications and Future Directionsmentioning
confidence: 97%